Geopolymer composites for the catalytic cleaning of tar in biomass-derived gas. (February 2019) - Bendoni, R.; Miccio, F.; Medri, V.; Benito, P.; Vaccari, A.; Landi, E.
Abstract: A novel application of geopolymers for the catalytic cleaning of biomass-derived syngas is reported. Powders of metal oxides, i.e. Fe2 O3 and Mn2 O3, were dispersed in a geopolymer matrix, to produce composites in granular form for fixed bed application. Additionally, a mixed Fe/Mn composite was produced to explore the combined effects of the two oxides. The activity of the new catalysts was investigated in real gasification conditions by means of a double fixed bed reactor, at 700, 800 and 900 °C. All the systems promoted an appreciable tar removal, while FE-SEM and MIP analyses demonstrated their stability at the process conditions. The best performances were obtained using the composite including both Mn and Fe oxides, which registered a tar decomposition up to 86% compared to inert sand, and 50% compared to olivine. A reasonable explanation was provided by TPR and XRD analyses, which pointed out an easier reducibility of this system. Graphical abstract: Highlights: Novel geopolymer-based catalysts with Fe2 O3 and Mn2 O3 . Low cost and green synthesis/disposal. Efficient tar decomposition at 700, 800 and 900 °C. Synergistic interaction of Mn2 O3 and Fe2 O3 .